2008
DOI: 10.1111/j.1601-0825.2007.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

The concentration of TNF‐α correlate with number of inflammatory cells and degree of vascularization in radicular cysts

Abstract: We believe that determination of TNF-alpha in cystic fluid simultaneously with other parameters can be an additional parameter for clinical diagnosis of inflammed cysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 21 publications
4
46
1
3
Order By: Relevance
“…Our data suggest higher values of CRP and TNF-α in DMT1 patients with developed microangiopathy in regard to DMT1 patients without microvascular complications. That fact is in accordance with literature data which indicate that higher value of infl ammatory cytokines correlates with microvascular and macrovascular damage [13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 82%
“…Our data suggest higher values of CRP and TNF-α in DMT1 patients with developed microangiopathy in regard to DMT1 patients without microvascular complications. That fact is in accordance with literature data which indicate that higher value of infl ammatory cytokines correlates with microvascular and macrovascular damage [13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 82%
“…The quantitative microscopic analysis was performed according to the method described by Jurisic et al 8 Each specimen was graded under 400× magnification as:…”
Section: Qualitative and Quantitative Microscopic Analysesmentioning
confidence: 99%
“…Thin capsules have a predominance of lymphocytes, whereas thick capsules are predominantly composed of plasma cells and macrophages. 8 Inflammatory cell count and degree of vascularization in periapical cysts have shown a strong association with increased expression of tumor necrosis factor-alpha (TNF-α), 8 indicating that inflammatory cells may have an important role in the development of these lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Jurisic, et al 13 (2008) showed a positive correlation between the concentration of TNF-α and the number of inflammatory cells in RCs. In agreement with the present study, Nonaka, et al 26 (2008) observed a lower number of immunopositive cells for VEGF in periapical lesions with few inflammatory infiltrate.…”
Section: Discussionmentioning
confidence: 99%